Crack propagation and coalescence in quasi-brittle materials at high temperatures. (January 2015) - Tang, S.B.; Tang, C.A.
Highlights: A thermo-mechanical-damage model is proposed for heterogeneous quasi-brittle material. The thermal cracking significantly depredates the residual strength of material. Shear fracture formed through the interaction and coalescence of tensile microcracks. The brittle–plastic damage model can study the mechanical behavior of material. The transient creep strain plays an important role in decreasing the axial stress. Abstract: A numerical model allowing for the thermo-mechanical analysis of quasi-brittle materials (concrete structures) at high temperatures via the finite element method and damage mechanics is presented. It incorporates a damage constitutive law to capture the initiation, propagation, coalescence and the interaction of cracks as a natural outcome of the calculated material response. Furthermore, the degradation of the mechanical properties due to temperature is estimated using a transient thermo-damage model. The numerical results obtained from the proposed model correspond well with those obtained in experimental tests performed by other authors on concrete specimens at high temperatures.